Efektivitas Penggunaan Pupuk Organik Cair Urin Kambing Terhadap Pertumbuhan Tanaman Terong Ungu (Solanum mengolena L) - Daru Setyo Rini; Agus Fahmi; Nanda Maulana Akbar (KAMBIUM Jurnal Pertanian, 2025)
This study aims to study the effectiveness of liquid organic fertilizer (POC) made from goat urine on the growth and yield of purple eggplant (Solanum melongena L.). The study was conducted in Keras Village, Diwek District, Jombang Regency, using a Randomized Block Design (RBD) with six treatments, namely P0 (control), P1 (NPK 4 g/plant), P2 (POC 100 ml/L), P3 (POC 150 ml/L), P4 (POC 200 ml/L), and P5 (POC 250 ml/L). Each treatment was repeated four times. The analysis of variance showed that the administration of goat urine POC significantly affected all observed parameters, including plant height, number of leaves, number of flowers, number of fruits, and fruit weight. The optimum dose was 250 ml/L of goat urine liquid organic fertilizer.